Sewage Sludge a Potential Source of Organic Amendment for Salt-affected Soils: Assessment of Ecotoxicological Risk Associated with Different Sources: Sewage sludge and ecotoxicological risk - Parul Sundha; Nirmalendu Basak; Arvind Kumar Rai; Priyanka Chandra; Sandeep Bedwal; Sanjay Kumar; Gajender Yadav (Journal of Soil Salinity and Water Quality, 2023)
Sewage sludge has pontential for application as an organic amendment and source of plant nutrition. This study was conducted to investigate the physico-chemical charecteristics and associated ecotoxicological risk associated with sewage sludge collected from cities of different level of industrial activities in Haryana. Electrical conductivity (EC1:5) of sludge ranged from 4.1 to 8.6 dS m-1 and sludge from Yamunanagar and Ballabhgarh had higher EC values (8.2-8.6 dS m-1). The organic carbon, nitrogen, phosphorus and potassium content were in the range of 8.8-27.2 %, 0.4-0.9%, 393.9-1117.5 mg kg-1 and 0.5-1.1%, respectively, whereas sludge from Gharaunda and Indri had low heavy metal contents and potential ecological risk index was 32.5 and 28.8, respectively. Sewage sludge from Yamunanagar, Faridabad and Ballabhgarh had high concentration of Cd, Ni and Cr and potential ecological risk index was in the range of 679-2749. It was concluded that sewage sludge from the Indri and Gharaunda had low ecological risk and had potential for agricultural application. However, industrial cities like Yamunanagar, Faridabad, Ballabhgarh need efficient mechanism for segregation of domestic and industrial effluents to avoid accidental mixing responsible for higher ecological risk associated with sludge from sewage treatment plants. This could be an emerging option for land restoration in low/marginal lands with low fertility especially in semi-arid areas.